The Expansion of Bank Credit - Angell, James W.; Ficek, Karel F. (Journal of Political Economy, 1933)
Introduction. The problem; definitions, page I.–I. The expansion of a single bank, page 3.–II. The expansion of the aggregate of commercial banks, page 15.–III. Observations on the single-bank and system coefficients, page 26. To Follow in Next Issue IV. The effect of central banking; the ratio of commercial bank credit to gold. –V. Observations on the member-bank system coefficients.–VI. Summary; conclusions.